An Analysis of Deixis in The Lyrics of A Song “Man Upon The Hill” by The Stars and Rabbit - Anggraeni, Mita Nur; Husnussalam, Hendra (PROJECT (Professional Journal of English Education), 2025)
The purpose of this study is to analyze the predominant deixis and the form of deixis found in the famous band Stars and Rabbit song "Man Upon The Hill". This study uses a qualitative method, data collection using document analysis techniques is done by reading, and writing. This study collected the data by doing the following: First, the researcher listened to the songs, second the researcher searched the internet for scripts for the lyrics of the song, third the researcher selected lyrics to analyze, fourth the researcher marked all the lyrics selected for analysis. After collecting the data from the lyrics script, the researcher analyzes the data are as follows: First, the researcher identifies several phrases that include deictic phrases. Second, the researcher classifies the identified deictic expressions according to their criteria. Third, the researcher analyzes the types of deixis. The results showed that there are three kinds of deixis in the lyrics of the song "Man Upon The Hill" that is person deixis in table 1, spatial deixis in table 2, and discourse deixis in table 3. However, the most common kinds of deixis used in the song "Man Upon the Hill" is a person deixis with 21 data. Compared with spatial deixis which consists of five words, and discourse deixis which consists of two words. So, that's what this song means, that's what the vocals experience.